Pengaruh Desentralisasi Fiskal, Fiscal Stress, Terhadap Pertumbuhan Ekonomi Dengan Kinerja Keuangan Sebagai Variabel Intervening Di Provinsi Bali Pada Masa Pandemi Covid-19 - Zainatun Fajria; Budi Wahono; Eka Farida (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine and analyze the effect of fiscal decentralization, fiscal stress on economic growth with financial performance as an intervening variable. The data analysis method used in this research is quantitative data analysis using path analysis. The data used is secondary data. The secondary data in this study are financial reports in the province of Bali during the COVID-19 pandemic.The results of this study indicate that the variable of fiscal decentralization has no significant negative effect on financial performance. Fiscal stress variable has no significant positive effect on financial performance. Fiscal decentralization variable has no significant positive effect on economic growth. Fiscal stress variable has a positive and significant effect on economic growth. The financial performance variable has a positive and significant effect on economic growth. The variable of Fiscal Decentralization on Economic Growth has no effect so that Financial Performance cannot mediate Fiscal Decentralization on Economic Growth. Meanwhile, Fiscal Stress on Economic Growth has no effect so that Financial Performance cannot mediate Fiscal Stress on Economic Growth in Cities/Regencies in Bali Province in 2014-2020. Keywords: Fiscal Decentralization, Fiscal Stress, Financial Performance, Economic Growth.